2020
DOI: 10.1016/j.cell.2020.05.018
|View full text |Cite
|
Sign up to set email alerts
|

An Autonomous Oscillation Times and Executes Centriole Biogenesis

Abstract: Highlights d Centriolar Plk4 levels oscillate and act as a switch for centriole biogenesis d Oscillations may be generated via an Asl/Plk4 delayed negative feedback loop d Plk4 oscillations are entrained and phase-locked by the Cdk/ Cyclin oscillator (CCO) d Plk4 oscillations can drive centriole biogenesis even when the CCO is perturbed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(101 citation statements)
references
References 85 publications
1
96
1
Order By: Relevance
“…These results suggest that phosphorylation of NEDD1 by PLK4 is critical for NEDD1 to switch its binding target from γ-TuRC to SAS-6 to facilitate cartwheel assembly initiation. Recent research has revealed that an autonomous PLK4 oscillation at the base of the growing centriole initiates and executes centriole biogenesis in fly embryos, and while S phase progresses, the centriolar PLK4 level grows to a critical concentration that triggers its destruction until its concentration is too low to support Sas-6 and Ana2 recruitment for cartwheel growth ( Aydogan et al, 2020 ; Aydogan et al, 2018 ). In addition, another study showed that reduced PLK4 activity relieves the SCF–FBXW5 complex activity to degrade centriolar SAS-6 to restrict centrosome reduplication ( Puklowski et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that phosphorylation of NEDD1 by PLK4 is critical for NEDD1 to switch its binding target from γ-TuRC to SAS-6 to facilitate cartwheel assembly initiation. Recent research has revealed that an autonomous PLK4 oscillation at the base of the growing centriole initiates and executes centriole biogenesis in fly embryos, and while S phase progresses, the centriolar PLK4 level grows to a critical concentration that triggers its destruction until its concentration is too low to support Sas-6 and Ana2 recruitment for cartwheel growth ( Aydogan et al, 2020 ; Aydogan et al, 2018 ). In addition, another study showed that reduced PLK4 activity relieves the SCF–FBXW5 complex activity to degrade centriolar SAS-6 to restrict centrosome reduplication ( Puklowski et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is in this model system where an organelle ‘clock’ has recently been demonstrated to regulate the timing of centriole formation – an oscillatory mechanism that is normally entrained by the cell cycle progression, but can also run autonomously ( Aydogan et al, 2020 ; Figure 2 ). Centrioles are cytoskeletal organelles that form centrosomes – the major microtubule organizing centers (MTOCs) that aid the assembly of mitotic spindles in dividing cells (reviewed in Banterle and Gönczy, 2017 ; Conduit et al, 2015 ).…”
Section: The Emerging Concept Of Autonomous Clocks and Their Mechanisms At Different Scales And Complexitiesmentioning
confidence: 99%
“…Biological oscillators can also entrain each other to create an oscillator hierarchy. This is the case with the circadian oscillators in peripheral organs, which take their cue from the master circadian oscillator in the brain (Brown et al, 2019), and the PLK4driven centriole biogenesis oscillator, which is entrained by the cell-cycle oscillator (Aydogan et al, 2020).…”
Section: Entrainmentmentioning
confidence: 99%
“…Circadian oscillators ( Bell-Pedersen et al, 2005 ) and Cyclin/CDK cell cycle oscillators ( Örd and Loog, 2019 ) are perhaps the best known examples of this style of clock, but oscillators are also found in other contexts in which biological processes are regularly repeated or require periodicity. Take, for example, the formation of a new procentriole during centriole duplication in Drosophila embryos ( Aydogan et al, 2020 ). The amount of material integrated into the new procentriole is controlled by oscillations in the recruitment of the master regulator Polo-like kinase 4 (PLK4) by its receptor Asterless.…”
Section: The Fundamentals Of Cellular Clocksmentioning
confidence: 99%